Management of Forgotten, Encrusted, and Fragmented Double-J Ureteral Stents: A Prospective Cross-Sectional Observational Study from a Tertiary Care Center. - Krishna, Dr. Chenna Sai; Jayaraju, Dr Juturu; Bangla, Dr Gidion (Student's Journal of Health Research Africa, 2026)
Background: Forgotten, encrusted, and fragmented double-J ureteral stents represent a preventable yet clinically demanding urological problem. Delayed retrieval increases the risk of stone formation, infection, fragmentation, and the need for combined endourological procedures. Objectives: To evaluate the clinical presentation, pattern of stent encrustation or fragmentation, management strategies, and short-term outcomes among patients treated for forgotten double-J ureteral stents at a tertiary care center. Methods: This prospective observational study included 22 consecutive patients managed at A C Subba Reddy Government Medical College & Hospital, Dargamitta, Nellore, Andhra Pradesh, India, from April 01, 2026, to April 30, 2026. Demographic details, symptoms, stent duration, imaging findings, operative procedures, complications, and clearance outcomes were analysed descriptively. Results: The mean age was 43.6 ± 12.8 years, and females constituted 54.5% of the cohort. The mean retained stent duration was 19.4 ± 9.7 months. Flank pain was the most frequent symptom. Encrusted-only stents were seen in 59.1%, while 27.3% had both encrustation and fragmentation. Ureteroscopy, cystolithotripsy, retrograde intrarenal surgery, and percutaneous nephrolithotomy were used according to encrustation burden. Complete stent clearance was achieved in all patients, with stone-free status in 90.9%. Conclusion: Multimodal endourological management provided high clearance with acceptable morbidity in patients with forgotten, encrusted, and fragmented double-J stents. Recommendations: Structured stent registries, patient counselling, and reminder systems should be implemented to prevent prolonged indwelling time and reduce avoidable complications.